Educação física escolar na educação infantil : a formação em questão - Dudeck, Tamara Suellen (2014)
The objective of this study is to identify what and how they are planned and organized knowledge / wisdom of Physical Education for Child Education by teachers who work in Higher Education to develop future teachers of Physical Education to Basic Education in one of the possible fields of teaching activity, the Child Education. For this carried out a bibliographic survey on the following aspects: conception of Childhood and Child Education, School Teacher Training for Child Education, School Teacher Training for Child Education in courses of Degree in Physical Education and Physical Education in Child Education. The descriptive and qualitative study investigated 7 degree courses in Physical Education, located in the state of Mato Grosso. Participants were 15 teachers working in Higher Education in public and private management institutions, who teaching in disciplines that discuss specific way abouy Child Education, as well as 138 students being finalized of the course. Documentary analysis of disciplines programs, interview guidelines directed at teachers and a questionnaire with open and closed questions directed to the students the courses of Degree in Physical Education in the state of Mato Grosso were used to collect data. It was identified that 6 about 7 courses present two disciplines and in just one, there is a discipline that discuss a specific way to Child Education. This indicates an advance for the Child Education in courses of Degree in Physical Education. We also observed a close relationship between the speech of teachers and the disciplines programs and yet, some teachers who have demonstrated a more enlightened view of humanizing education. However, when considering the specific issues of Physical Education for Child Education noted a still concern, supposedly veiled, about the biological discourse in most aspects. Students' responses to the questionnaires reflect the positioning of teachers and the proposals of disciplines programs, because the same emphasis on biological issues, with the exception the presence of ludicity, games and plays are presented, but what predominates is a confusing point of view of the didactic and pedagogical aspects. So, is essential to rethink and reorganize the knowledge/ wisdow of Physical Education for Child Education in the proposals contained in the documents that guide the disciplines and the understanding of the role of teachers of Physical Education at this level of teaching, considering the reality found.